The scream of the haunted mask - Stine, R. L. (New York : Scholastic, 2008)
Carly Beth, having survived one Halloween encounter with the Haunted Mask, is very troubled when the green, drooling rubber face begins calling out to her again.
Scream of the haunted mask -- Enter HorrorLand -- Fear file.
3.8
5-8
Keywords: Halloween -- Juvenile fiction; Masks -- Juvenile fiction; Halloween -- Fiction; Horror stories; Masks -- Fiction; Halloween -- Fiction; Horror fiction; Masks (Facial) -- Fiction; Horror fiction